Building Comprehension: A Step-by-Step Approach for High School EFL Students in Indonesia - Harfal, Zaldi; Ariyanfar, Somayyeh (Pijar : Jurnal Penelitian Bidang Pendidikan dan Pembelajaran, 2024)
A This study examines a structured instructional framework for teaching comprehension strategies to high school EFL students in Indonesia. It focuses on the challenges teachers face in fostering students' independent literacy skills by implementing Duke and Pearson’s (2002) five-step model: explicit instruction, collaborative learning, guided practice, gradual release of responsibility, and independent application. The framework integrates comprehension strategies like Summarizing and Chunking with instructional strategies such as Think-Pair-Share and Modeling to ensure effective classroom implementation. A lesson plan for a professional development workshop is proposed to train EFL teachers in applying these strategies. The findings show that a systematic approach enhances students' cognitive and metacognitive skills, enabling them to comprehend texts independently. The study recommends adapting this framework for younger learners and low-proficiency adult students to ensure its applicability across diverse learning contexts. This approach helps address gaps in literacy instruction and prepares students for academic and real-world challenges.